La virtualità digitale tra immanenze cronologiche e diversioni territoriali - De Feo, Linda (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
Object of reﬂection will be the present centrality of the concept of virtuality. It indicates what is potentially destined for probable realization and represents the transformations of experience. It will attempt to observe how this concept is today mainly referred to aprocess of digital change which touches all elements of the technological anthropic system. This system is constantly intent on rewriting itself and it is converted by electronic language into patterns of informations capable of redesigning space and time. Starting from a problematic core of tensions and ﬁnalities, digital virtuality interweaves material structures and simbolic-linguistic ﬁelds according to absolutely metaterritorial dynamics. It shapes the individual and collective life through the redeﬁnition of sensoriality and of cognition, and also the reconstruction of a communicative environments which disseminates redelined subjectivities. The results are a reworking the concept of proximity, new images of sociality and new formes of narrative, which mean new descriptions and interpretations of the infosfera.